Granulocyte functions are independent of arginine availability. Issue 6 (7th August 2014) - Kapp, Katharina; Prüfer, Steve; Michel, Christian S.; Habermeier, Alice; Luckner‐Minden, Claudia; Giese, Thomas; Bomalaski, John; Langhans, Claus‐Dieter; Kropf, Pascale; Müller, Ingrid; Closs, Ellen I.; Radsak, Markus P.; et al.
Abstract : Granulocyte viability, phagocytosis, IL‐8 secretion, chemotaxis, and antifungal activity are completely preserved in the absence of extracellular arginine. Abstract : Arginine depletion via myeloid cell arginase is critically involved in suppression of the adaptive immune system during cancer or chronic inflammation. On the other hand, arginine depletion is being developed as a novel anti‐tumor metabolic strategy to deprive arginine‐auxotrophic cancer cells of this amino acid. In human immune cells, arginase is mainly expressed constitutively in PMNs. We therefore purified human primary PMNs from healthy donors and analyzed PMN function as the main innate effector cell and arginase producer in the context of arginine deficiency. We demonstrate that human PMN viability, activation‐induced IL‐8 synthesis, chemotaxis, phagocytosis, generation of ROS, and fungicidal activity are not impaired by the absence of arginine in vitro. Also, profound pharmacological arginine depletion in vivo via ADI‐PEG20 did not inhibit PMN functions in a mouse model of pulmonary invasive aspergillosis; PMN invasion into the lung, activation, and successful PMN‐dependent clearance of Aspergillus fumigatus and survival of mice were not impaired. These novel findings add to a better understanding of immunity during inflammation‐associated arginine depletion and are also important for the development of therapeutic arginine depletion as anti‐metabolic tumor therapy.